The pretreatment albumin to globulin ratio predicts survival in patients with natural killer/T-cell lymphoma - Bi,Xi-wen; Wang,Liang; Zhang,Wen-wen; Yan,Shu-mei; Sun,Peng; Xia,Yi; Li,Zhi-ming; Jiang,Wen-qi (PeerJ, 2016)
Background. The pretreatment albumin to globulin ratio (AGR) has been reported to be a predictor of survival in several types of cancer. The aim of this study was to evaluate the prognostic impact of AGR in patients with natural killer/T-cell lymphoma (NKTCL). Methods. We retrospectively reviewed the available serum biochemistry results for 331 NKTCL patients before treatment. AGR was calculated as albumin/(total protein—albumin), and a cut-off value of 1.3 was used to define AGR as low or high. Survival analysis was used to assess the prognostic value of AGR. Results. A low AGR (<1.3) was associated with significantly more adverse clinical features, including old age, poor performance status, advanced stage, elevated lactate dehydrogenase, B symptoms, and high International Prognostic Index (IPI) and natural killer/T-cell lymphoma prognostic index (NKPI) scores. Patients with a low AGR had a significantly lower 5-year overall survival (44.5 vs. 65.2%, P < 0.001) and progression-free survival (33.1 vs. 57.4%, P < 0.001). In the multivariate analysis, a low AGR remained an independent predictor of poorer survival. Additionally, AGR distinguished patients with different outcomes in the IPI low-risk group and in the NKPI high-risk group. Discussion. Pretreatment AGR may serve as a simple and effective predictor of prognosis in patients with NKTCL.
Keywords: Albumin to globulin ratio; Extranodal natural killer/T-cell lymphoma; Prognosis; International prognostic index; Natural killer/T-cell lymphoma prognostic index